ARTIFICIAL INTELLIGENCE WITH LEGAL ASPECTS - Xayriddinov Parvizbek Baxtiyorovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation: This article looks at how artificial intelligence (AI) is becoming more common in today's world and how it is affecting many areas, such as law, education, business, and government. It analyzes the advantages and disadvantages of AI use from a legal perspective and proposes possible legal and regulatory solutions to address challenges such as privacy violations, bias, accountability, and employment issues. The article emphasizes the importance of developing effective legal frameworks and ethical standards to ensure responsible and safe use of artificial intelligence.